2016
DOI: 10.1371/journal.pone.0148600
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Attentional Targets under Covert Attention Lead to Paradoxically Enhanced Alpha Desynchronization in Neurofibromatosis Type 1

Abstract: The limited capacity of the human brain to process the full extent of visual information reaching the visual cortex requires the recruitment of mechanisms of information selection through attention. Neurofibromatosis type-1 (NF1) is a neurodevelopmental disease often exhibiting attentional deficits and learning disabilities, and is considered to model similar impairments common in other neurodevelopmental disorders such as autism. In a previous study, we found that patients with NF1 are more prone to miss targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Custom MATLAB (version R2017b, The MathWorks, USA) scripts were implemented [adapted from our previous works by Castelhano et al (Castelhano et al 2013) and by Silva et al (Silva et al 2016)] for the pre-processing and power quantification. Briefly, we conducted time-frequency analysis as reported by Uhlhaas et al (2006) and other works (Lachaux et al 1999;Rodriguez et al 1999;Uhlhaas et al 2006;Melloni et al 2007;Castelhano et al 2013), by applying the pseudo Wigner-Ville transformation.…”
Section: Eeg Data Acquisition and Analysismentioning
confidence: 99%
“…Custom MATLAB (version R2017b, The MathWorks, USA) scripts were implemented [adapted from our previous works by Castelhano et al (Castelhano et al 2013) and by Silva et al (Silva et al 2016)] for the pre-processing and power quantification. Briefly, we conducted time-frequency analysis as reported by Uhlhaas et al (2006) and other works (Lachaux et al 1999;Rodriguez et al 1999;Uhlhaas et al 2006;Melloni et al 2007;Castelhano et al 2013), by applying the pseudo Wigner-Ville transformation.…”
Section: Eeg Data Acquisition and Analysismentioning
confidence: 99%
“…As for EEG, it has been shown that NF1 children differ from matched controls during low level visual processing in term of alpha oscillation amplitude in the parieto-occipital cortex . EEG also highlighted differences between NF1 and controls during higher level attentional task as flanker task (Bluschke et al, 2017) and covert attentional task (Silva et al, 2016). As for fMRI, NF1 children showed reduced activation in a set of area within the salience network (i.e., inferior occipital gyrus, fusiform gyrus/posterior cerebellum, pre-SMA and inferior frontal gyrus) during a GO-NO GO task (Pride, Korgaonkar, North, Barton, & Payne, 2017).…”
mentioning
confidence: 82%
“…EEG also highlighted differences between NF1 and controls during higher level attentional task as flanker task (Bluschke et al, 2017) and covert attentional task (Silva et al, 2016). As for EEG, it has been shown that NF1 children differ from matched controls during low level visual processing in term of alpha oscillation amplitude in the parieto-occipital cortex .…”
mentioning
confidence: 85%
“…After running Independent Component Analysis (ICA), we removed components including blinks and eye movements. For power quantification, custom MATLAB (version R2017b, The MathWorks, U.S.) scripts were implemented [adapted from our previous studies by Castelhano et al ( 30 ) and by Silva et al ( 31 )], as described in our previous work in healthy participants ( 18 ). For quantification purposes, the baseline was defined between −2,000 ms and 0 for the eyes' closure and opening, and between −2,000 and −1,500 ms, before movement, for the motor tasks.…”
Section: Methodsmentioning
confidence: 99%